Canaloplasty with Suprachoroidal Drainage in Patients with Pseudoexfoliation Glaucoma – Four Years Results. (1st February 2021) - Seuthe, Anna-Maria; Szurman, Peter; Januschowski, Kai
ABSTRACT: Purpose : To evaluate the long-term efficacy and safety of the modified canaloplasty technique with additional suprachoroidal drainage in patients with pseudoexfoliation glaucoma. Methods : This retrospective clinical trial included 131 patients with pseudoexfoliation glaucoma who underwent canaloplasty with suprachoroidal drainage (scD). One hundred and eleven of 131 patients underwent the follow-up examination after 48 months. Primary endpoints were the pressure-lowering and drug-sparing effect as well as the success rates. Secondary endpoints were intra- and postoperative complications and the occurrence of secondary surgical interventions. Results : The IOP was reduced by 45.8% after 12 months (from baseline 23.4 ± 5.1 mmHg to 12.7 ± 2.2 mmHg) and by 45.1% after four years (12.8 ± 2.2 mmHg) ( p < .001). The mean number of IOP-lowering medication decreased significantly from 3.4 at baseline to 0.6 after 12 months and to 1.0 after four years. The IOP-reducing effect was even stronger in those cases in whom canaloplasty+ scD was combined with cataract surgery (49.4% after 12 months and 47.6% after four years). No serious complications were observed. Conclusions : The modified surgery technique of canaloplasty with suprachoroidal drainage is a safe and effective way of reducing IOP in patients with pseudoexfoliation glaucoma.